gp130 cytokines are positive signals triggering changes in gene expression and axon outgrowth in peripheral neurons following injury - Zigmond, Richard (Frontiers in Molecular Neuroscience, 2012)
Adult peripheral neurons, in contrast to adult central neurons, are capable of regeneration after axonal damage. Much attention has focused on the changes that accompany this regeneration in two places, the distal nerve segment (where phagocytosis of axonal debris, changes in the surface properties of Schwann cells, and induction of growth factors and cytokines occur) and the neu-ronal cell body, where dramatic changes in cell morphology and gene expression occur. The changes in the axotomized cell body are often referred to as the “cell body response”. The focus of the current review is a family of cytokines, the gp130 cytokines, which have been clearly shown to function as injury signals for axotomized neurons, triggering changes in gene expression and in neurite outgrowth. These cytokines play an important role in the response to injury of sympathetic, sensory, and motor neurons. Recent studies suggest that manipulation of this cyto-kine system can also produce some regeneration by injured central neurons.